Practical Ethics Given Moral Uncertainty. Issue 3 (September 2019) - MacAskill, William
Abstract: A number of philosophers have claimed that we should take not just empirical uncertainty but also fundamental moral uncertainty into account in our decision-making, and that, despite widespread moral disagreement, doing so would allow us to draw robust lessons for some issues in practical ethics. In this article, I argue that, so far, the implications for practical ethics have been drawn too simplistically. First, the implications of moral uncertainty for normative ethics are far more wide-ranging than has been noted so far. Second, one can't straightforwardly argue from moral uncertainty to particular conclusions in practical ethics, both because of 'interaction' effects between moral issues, and because of the variety of different possible intertheoretic comparisons that one can reasonably endorse.